A green, efficient and precise hydrogen therapy of cancer based on in vivo electrochemistry. Issue 3 (5th December 2019) - Qi, Guohua; Wang, Bo; Song, Xiangfu; Li, Haijuan; Jin, Yongdong
Abstract: By combined use of traditional Chinese acupuncture Fe needle electrode and in vivo electrochemistry, we achieved in vivo H2 generation in tumors in a controllable manner and exploited it for effective and green therapy of tumors for the first time. The cathodic acupuncture electrodes working under an applied voltage of ∼3 V (with minimal damage to the living body) undergo effective electrochemical reactions in the acidic tumor area that produce sufficient H2 locally to cause cancer cells to burst and die. Due to puncture positioning, the acidic tumor microenvironment and gas diffusion effect, the developed H2 generation electrochemotherapy (H2 -ECT) strategy enables precise and large-scale tumor therapy, as demonstrated by in vivo treatment of diseased mice (glioma and breast cancers). Such green H2 -ECT is simple, highly efficient and minimally invasive, requiring no expensive medical equipment or nano materials and medication, and is therefore very promising for potential clinical applications.